Imagined, embodied and actual Turks in Early Modern Europe - Holm, Bent; Rasmussen, Mikael Bøgh (Ottomania, 2021)
The confrontation between European countries and the expanding Ottoman Empire in the early modern era has played a major role in numerous fields of history. The aim of this book is to investigate the European-Ottoman interrelations from three angles. One deals with the circumstances: How did the Europeans meet the Turks in pragmatic and diplomatic connections? Another concerns imagery: how were the Turks depicted in literature and art? The third examines performativity: how were the Turks inserted into plays, operas and ceremonies? This book confronts mental, visual and embodied images with historical positions and conditions. The focus, therefore, is on the dynamic interactive processes of experience, embodiment and imagination in context. Bringing together Turkish and European scholars, it applies a number of research strategies used by historians to the history of art, literature, music and theatre.